Evaluating an International Class Initiative Program in EFL Higher Education: A CIPP Model Analysis - A. A. Gede Yudha Paramartha; Ni Nyoman Padmadewi; I G A Lokita Purnamika Utami; Putu Suarcaya (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study evaluated the implementation of the International Class Initiation (IKI) program within the English Language Education department at Universitas Pendidikan Ganesha (Undiksha) using Stufflebeam’s Context, Input, Process, and Product (CIPP) model. Methodology: This mixed-methods study operationalized CIPP framework. For Context evaluation document analysis was assessed to evaluate policy alignment. For Input Evaluation observation was done to assess the infrastructure and document analysis for assessing the curriculum. Process evaluation focused on instructional quality and EMI consistency collected through surveys. Product evaluation focused on measuring students GPAs as well as mapping students co-curricular achievements. Main Findings: Context and input evaluations revealed positive alignment with Indonesia’s Key Performance Indicators (IKU 8) and the university's vision, supported by strict selection criteria and improved classrooms. Process evaluation demonstrated high pedagogical clarity and consistent English instruction, though it highlighted an affective support gap by the lecturers. Product evaluation empirically proved: IKI students achieved significantly higher GPAs (p < 0.05), secured 38.9% of student awards despite a unequal class distribution ratio, and recorded 15 international mobility placements, including dual-degree programs. Novelty/Originality of this study: This study’s novelty lies in its multi-dimensional evaluation of an International Class Initiative. It uniquely integrates qualitative policy analysis and quantitative instructional surveys with empirical evidences of infrastructure, academic and non-academic achievements, and international mobility outcomes. This comprehensive approach offers a complete picture of how CIPP can be used to evaluate "Internationalization at Home" program.